Development of a photo-crosslinkable diaminoquinazoline inhibitor for target identification in plasmodium falciparum - Lubin,AS; Zubiaurre,AR; Matthews,H; Baumann,H; Fisher,FR; Morales-Sanfrutos,J; Hadavizadeh,KS; Nardella,F; Tate,EW; Baum,J; Scherf,A; Fuchter,MJ (ACS Infectious Diseases, 2018)
Diaminoquinazolines represent a privileged scaffold for antimalarial discovery, including use as putative Plasmodium histone lysine methyltransferase inhibitors. Despite this, robust evidence for their molecular targets is lacking. Here we report the design and development of a small-molecule photo-crosslinkable probe to investigate the targets of our diaminoquinazoline series. We demonstrate the effectiveness of our designed probe for photoaffinity labelling of Plasmodium lysates and identify similarities between the target profiles of the probe and the representative diaminoquinazoline BIX-01294. Initial pull-down proteomics experiments identified 104 proteins from different classes, many of which are essential, highlighting the suitability of the developed probe as a valuable tool for target identification in Plasmodium falciparum.